PENGARUH PERPUTARAN PERSEDIAAN TERHADAP RETURN ON INVESTMENT (ROI) PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DALAM LQ45 DI BURSA EFEK INDONESIA (BEI) (Studi Kasus Pada PT. Indofood CBP Sukses Makmur Tbk. dan PT. Indofood Suk - ., Supramono (MONETER, 2016)
Analysis of the financial statements is of fundamental importance in assessing the performance of a company in the benefit. For that we needed a tool the form of the ratio of that can be used to measure the level of efficiency as well as the existence of a business. One of the ratio of that can be used very important in the measurement of financial performance in the benefit is the ratio of return on investment. This ratio can be determined by the company's ability to generate profits from assets owned by the company. The purpose of this study was to examine the influence of inventory turnover variable to the return on investment (ROI) period 2010-2016. The method used in this research is quantitative method with a sample of manufacturing company sub-sector food and drink registered in LQ45 listed in Indonesia Stock Exchange (IDX).The sampling technique used purposive sampling with criteria (1) The manufacturing company listed on the Stock Exchange and is always present financial statements December 31 fiscal year during the study period, (2) The company must have a listing at the beginning of the study and did not delisted until the end of the study period, (3) From the beginning of the study period until the end of the study period resulted in a positive earnings. Based on the research result show that inventory turnover significant effect on ROI, the result of significant as 0,000 (<0,05). With the result corelation as 0.909 it’s mean exist context is very strong, while the result of determination as 82,6%. And the result from hypotesys, is t’arithmatic’ as 7,222 and t’table’ as 2,201 (t’arithmatic’ > t’table’) it’s mean inventory turnover influental to ROI.